Innovative approaches to the management of patients with obstructive sleep apnea-hypopnea syndrome, obesity and hypertension - L.V. Radetska; A.I. Khomitska; T.I. Krytskyy; O.O. Chukur; A.O. Bob; N.V. Pasiechko; N.I. Yarema; L.V. Naumova (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Obstructive sleep apnea-hypopnea syndrome (OSAHS) is characterized by recurrent episodes of partial or complete upper airway collapse during sleep that is highlighted by a reduction or complete cessation of airflow despite documented ongoing inspiratory efforts. There are some pharmacological treatments for daytime sleepiness caused by OSASH. Identifying and treating obstructive sleep apnea early is important to reduce the risks of future complications. The purpose of the study was to determine the functional state of the cardiovascular system and the oxygen state of body tissues in patients with OSAHS of varying severity. Materials and methods. The study included 109 participants (85 men and 24 women) aged 27 to 55 (mean of 46.4 ± 9.1) years. All patients were comparable in sex, age, anthropometric parameters, as well as in the history of hypertension and the level of office blood pressure and underwent a study of the oxygen state by pulse oximetry and oximetry. Results. Hypertension in patients with obstructive sleep apnea-hypopnea syndrome is more resistant to therapy. The degree of resistance depends on the severity of OSAHS. The analysis of daily blood pressure monitoring data in OSAHS revealed differences in the growth of mean blood pressure, hypertension time index and daily blood pressure profile. The degree of night blood pressure reduction in patients with severe OSAHS was lower, among them, individuals with non-dipper and night-peaker profiles predominated. Conclusions. In OSAHS, significant disorders of arterial and venous blood oxygenation were detected, which is confirmed by a reliable decrease in venous blood saturation (p < 0.01) and oxygen content in arterial blood (p < 0.01). The volume of oxygen consumed by peripheral tissues was significantly lower (p < 0.05) in patients with severe OSAHS.